Cupido osiris (Lepidoptera, Rhopalocera): an overlooked species of the Slovenian butterfly fauna - Rudi Verovnik (Natura Sloveniae)
There are only a few historical records of the Osiris Blue from Slovenia, and two are plausible based on the species habitat requirements. The record from gravel banks of the Sava River north of Ljubljana has been confirmed by a single female preserved in the collection of the Slovenian Museum of Natural History. Additionally, several collected specimens from Potoče village in the Vipava Valley indicate its wider distribution in the past. Currently, the species is confined to a narrow belt of the Kraški rob between Predloka and Mt. Lipnik. The habitat requirements of the species and its threat status in Slovenia are discussed.